Institutional arrangements in the promotion of sustainable livestock: an approach from the case of beef and dairy cattle production chains in Jalisco, Chiapas, and Campeche - Avalos, Ileana; Sepulveda, Claudia; Betanzos, Juan Edduardo; Jimenes-Trujillo, Jose Antonio; Perez-Sanches, Edwin; Escobedo, Adriana (Frontiers in Sustainable Food Systems, 2024)
This study focuses on a policy and practice review of existing institutional arrangements within the beef and dairy cattle production sectors in the Mexican states of Jalisco, Chiapas, and Campeche. Acknowledging the critical role of robust governance frameworks in transitioning towards sustainable livestock agriculture, a collaborative governance approach is employed to holistically address environmental and production challenges. This approach underscores the importance of active participation, stakeholder collaboration, and contextual adaptation in decision-making processes.Classified as explanatory research, the study is grounded in a qualitative approach, covering a synchronous period from 2017 to 2022. Secondary sources such as public policies, international climate commitment reports, sector-specific reports, and databases were utilized to provide context and data regarding the analyzed institutional arrangements. Additionally, semi-structured informationgathering protocols were developed and, in conjunction with participant observation, administered to approximately 30 key stakeholders from public, private, academic, research centers, international cooperation, and civil society sectors involved in institutional arrangements in the aforementioned states.The findings highlight the significance of collaborative governance as a valuable alternative for addressing governance challenges in the livestock sector, particularly when hierarchical or marketoriented approaches are less effective. The diversity of identified institutional arrangements, ranging from hierarchical to polyarchic, emphasizes the need to acknowledge the specificities of the context in which they operate and adapt strategies accordingly. This analysis contributes to the growing discussion on sustainable livestock farming and the fundamental role of institutional arrangements in promoting responsible practices and mitigating environmental impacts. As demands for natural resources and environmental awareness increase, understanding and strengthening these arrangements become essential to balance livestock production and environmental conservation.